Production, safety and efficacy of iPSC-derived mesenchymal stromal cells in acute steroid-resistant graft versus host disease: a phase I, multicenter, open-label, dose-escalation study - Bloor, Adrian J. C.; Patel, Amit; Griffin, James E.; Gilleece, Maria H.; Radia, Rohini; Yeung, David T.; Drier, Diana; Larson, Laurie S.; Uenishi, Gene I.; Hei, Derek; Kelly, Kilian; Slukvin, Igor; et al. (Nature medicine, 2020)
The therapeutic potential of donor-derived mesenchymal stromal cells (MSCs) has been investigated in diverse diseases 1 , including steroid-resistant acute graft versus host disease (SR-aGvHD) 2 . However, conventional manufacturing approaches are hampered by challenges with scalability and interdonor variability, and clinical trials have shown inconsistent outcomes 3 , 4 . Induced pluripotent stem cells (iPSCs) have the potential to overcome these challenges, due to their capacity for multilineage differentiation and indefinite proliferation 5 , 6 . Nonetheless, human clinical trials of iPSC-derived cells have not previously been completed. CYP-001 (iPSC-derived MSCs) is produced using an optimized, good manufacturing practice (GMP)-compliant manufacturing process. We conducted a phase 1, open-label clinical trial (no. NCT02923375) in subjects with SR-aGvHD. Sixteen subjects were screened and sequentially assigned to cohort A or cohort B ( n = 8 per group). One subject in cohort B withdrew before receiving CYP-001 and was excluded from analysis. All other subjects received intravenous infusions of CYP-001 on days 0 and 7, at a dose level of either 1 × 10 6 cells per kg body weight, to a maximum of 1 × 10 8 cells per infusion (cohort A), or 2 × 10 6 cells per kg body weight, to a maximum dose of 2 × 10 8 cells per infusion (cohort B). The primary objective was to assess the safety and tolerability of CYP-001, while the secondary objectives were to evaluate efficacy based on the proportion of participants who showed a complete response (CR), overall response (OR) and overall survival (OS) by days 28/100. CYP-001 was safe and well tolerated. No serious adverse events were assessed as related to CYP-001. OR, CR and OS rates by day 100 were 86.7, 53.3 and 86.7%, respectively. The therapeutic application of iPSC-derived MSCs may now be explored in diverse inflammatory and immune-mediated diseases. A GMP-compliant process for generating human iPSC-derived mesenchymal stromal cells tested in a phase 1 trial is safe and well tolerated in subjects with acute steroid-resistant graft versus host disease.